2019
DOI: 10.1021/acs.jced.9b00527
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Thermodynamic Parameters for Alkyl Benzyl Dimethyl Ammonium Chloride and Cetyl Trimethyl Ammonium Chloride Surfactants in Water and Alcoholic-Water Solvents

Abstract: The conductivity of both alkyl benzyl dimethyl ammonium chloride (BAC) and cetyl trimethyl ammonium chloride (CTAC) surfactants in water and in alcoholic-water mixed solvents (methanol, ethanol, and glycerol) with different mole fractions of alcohols has been measured at temperatures (298.15, 303.15, 308.15, and 313.15 K). From the measured data of conductivity and surface tension, the critical micelle concentration (cmc) of both BAC and CTAC was determined. The cmc was found to increase as the temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…This CTMA‐Cl solution had a concentration above CMC of CTMA‐Cl at 25 °C, therefore its surface tension was close to the surface tension of CTMA‐Cl at CMC (ca. 40.5 mN m −1 at 25 °C) [39] . The surface tension of the dispersion TD102 decreased to 40±0.2 mN m −1 at 25 °C by adding CTMA‐Cl to reach a concentration of CTMA‐Cl of 8.5 mg mL −1 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This CTMA‐Cl solution had a concentration above CMC of CTMA‐Cl at 25 °C, therefore its surface tension was close to the surface tension of CTMA‐Cl at CMC (ca. 40.5 mN m −1 at 25 °C) [39] . The surface tension of the dispersion TD102 decreased to 40±0.2 mN m −1 at 25 °C by adding CTMA‐Cl to reach a concentration of CTMA‐Cl of 8.5 mg mL −1 .…”
Section: Resultsmentioning
confidence: 96%
“…40.5 mN m À1 at 25 8 8C). [39] Thes urface tension of the dispersion TD102 decreased to 40 AE 0.2 mN m À1 at 25 8 8C by adding CTMA-Cl to reach aconcentration of CTMA-Cl of 8.5 mg mL À1 .T hese results showed that the dispersions did not contain micelles of CTMA-Cl.…”
Section: Angewandte Chemiementioning
confidence: 86%
“…Surfactants are significant for the scientific world and have many application areas in industry and laboratories. Agrochemical, pesticides, textile, cosmetics, herbicides, biotechnology, detergents, pharmaceuticals, medicals, mineral flotation, food processing, nanotechnology, paint, petroleum, drug delivery, improved oil recovery, and agriculture are some surfactant applications commonly used in industry. …”
Section: Introductionmentioning
confidence: 99%